Increasing Novice EFL Learners’ Vocabulary based on Short Islamic Stories in an Islamic Higher Education - Paramma, Muhammad Azwar; Shafa, Shafa (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
The majority of EFL students lack adequate vocabulary knowledge and become frustrated when they cannot comprehend the meaning of key vocabulary terms in a passage. The study aims to determine whether short Islamic stories can improve the vocabulary acquisition of novice EFL learners. It uses quantitative research by applying a pre-experimental design with a pre-test and post-test. The study involves 30 novice EFL students enrolled in the Basic Translation course at the English Language Education department, Islamic State University of Sultan Aji Muhammad Idris Samarinda. To determine the significance of the short Islamic study to the student's vocabulary significance, the study applied a vocabulary test containing a matching test, a word meaning test, a vocabulary test, and a pronunciation and spelling test. The findings of the study revealed a significant difference between the pre-test and post-tests due to the treatment. The study's results refuted the null hypothesis. It was determined that there was substantial evidence regarding the effect of Islamic short stories on vocabulary acquisition. Further studies related to this study are needed considering the data provided in this pre-experimental design is still limited to the number of treatment groups.